A review of alpha activity in integrative brain function: Fundamental physiology, Sensory coding, cognition and pathology - BAŞAR, EROL (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2012)
Aim of the review: Questions related to the genesis and functional correlates of the brain's alpha oscillations around 10 Hz (Alpha) are one of the fundamental research areas in neuroscience. In recent decades, analysis of this activity has been not only the focus of interest for description of sensory-cognitive processes, but has also led to trials for establishing new hypotheses. The present review and the companion review aim to constitute an ensemble of "reasonings and suggestions" to understand alpha oscillations based on a wide range of accumulated findings rather than a trial to launch a new "alpha theory". Surveyed descriptions related to physiology and brain function: The review starts with descriptions of earlier extracellular recordings, field potentials and also considers earlier alpha hypotheses. Analytical descriptions of evoked and event-related responses, event-related desynchronization, the relationship between spontaneous activity and evoked potentials, aging brain, pathology and alpha response in cognitive impairment are in the content of this review. In essence, the gamut of the survey includes a multiplicity of evidence on functional correlates in sensory processing, cognition, memory and vegetative system, including the spinal cord and heart. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: EEG; Alpha; Evoked Alpha; Event Related Alpha; Event Related Oscillations; Memory; Child EEG; Aging; Cognitive Impairment; Emotion; Pre-Stimulus Alpha; Evoked Coherences; Event Related Coherences; Event-related Potentials; Auditory Oddball Task; Sympathetic-Nerve Discharge; Compound Field Potentials; Visual Evoked-Response; Recorded Eeg-Epograms; Short-Term-Memory; Alzheimers-Disease; Reticular-Formation; Normal-Children; Uyarılmış Alfa; Olaya İlişkin Alfa; Olaya İlişkin Salınımlar; Bellek; Çocuk EEG; Yaşlanma; Kognitif Bozukluk; Duygu; Ön-Uyaran Alfa; Uyarılmış Eşdurum; Olaya İlişkin Eşdurum; Olaya İlişkin Potansiyeller; İşitsel Oddball Görev; Sempatik Sinir Deşarj; Bileşik Alan Potansiyelleri; Görsel Uyarılmış-Cevap; Kaydedilen EEG-Epograms; Kısa Süreli Hafıza; Alzheimer Hastalığı; Retiküler Oluşumu; Normal Çocuklar